Effects of feeding a heat processed, predigested liquid diet to three-week old weanling pigs - S F Binder; E R Skoch; C W Deyoe; G L Allee; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1978)
One hundred forty, three-week old weanling pigs were used to evaluate the effects of feeding a heat-processed, predigested liquid diet. In Trial I, pigs were randomly allotted to a dry crumbled diet or a processed liquid diet. The basal corn-soybean meal diet contained 20% protein. A preference trial and a digestion trial were also conducted using the same treatments. A second feeding trial was conducted using a basal diet which contained 30% whey. Treatments consisted of a dry meal diet, a dry meal + water diet, and a processed liquid diet.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Predigested liquid diet; Weanling pigs